Pemenuhan Hak Warga Binaan atas Pelayanan Kesehatan di Lembaga Pemasyarakatan - Ode, Mirjan; Anwar, Arman; Leasa, Elias Zadrach (Faculty of Law Universitas Pattimura, 2024)
Indonesia is a country of law, if anyone commits a violation of the law, they will be subject to a crime and become a state prisoner to serve their sentence. Those who become state prisoners are usually referred to as inmates. When inmates become state prisoners, their rights as human beings are revoked, so the state must guarantee their rights while they are in prison. Article 9 of Law No. 22 of 2022 concerning Corrections guarantees the rights of inmates, especially the right to receive services. health, the right to health is regulated in Article 4 paragraph (1) of Law no. 17 of 2023 concerning Health. The existence of regulations regarding the rights of inmates, the state must fulfill the rights to health services for inmates as well as possible. However, sometimes the rights of inmates are not implemented properly, such as cases of inmates who died because they were too late in being given first aid and cases of inmates who died because they were referred to hospital too late. This shows that the rights of inmates are still not fulfilled, especially the right to health services. Based on the results of research conducted, the regulation of inmates' rights to health services in correctional institutions, especially in Ambon Class IIA prisons, has been running quite well, starting from the availability of health human resources, the availability of medicines, the availability of health services, the availability of food and drink, and the availability of other health service programs in prisons, then inmates can access health services in prisons provided by the state, starting from physical and economic health services where all costs of health services for inmates are borne by the state. With the existence of rights to health services, the state is obliged to be responsible for fulfilling the right to health services to respect, protect and fulfill them. If the inmates' rights to health services in correctional institutions are not fulfilled, the inmates have the right to submit complaints and/complaints to the prison authorities. The legal mechanism that can be taken by inmates due to the failure to fulfill their rights to health services in prisons is contained in the decision of the Director General of Corrections. No. E.22.PR.08.03 of 2001 concerning Implementation of Correctional Duties. The mechanism is that the prison and the inmates' guardians will hold a hearing to resolve the matter.